Mengurai Ironi Agraris: Kesejahteraan, Struktur Lahan, dan Sensus Pertanian 2023 (Aceh) - Mayhilda Nitami; Nurita Puri; Uswatun Hasanah Nura (SIMBIOSIS: Jurnal Sains Pertanian, 2025)
This study examines the agrarian paradox in Aceh Province by focusing on the relationship between land structure, farmer welfare, and the 2023 Agricultural Census results. Despite Aceh’s vast agricultural land potential, farmer welfare has not significantly improved. Using a quantitative approach, multiple linear regression analysis was applied to test the effects of land size, land ownership structure, access to capital, market access, and technology usage on farmers' income. Data were sourced from the official Agricultural Census by BPS Aceh Province. Results show that land structure, capital access, and technology use significantly influence farmers' income with coefficients of 0.45, 0.30, and 0.25, respectively. Market access had a positive but insignificant effect. Diagnostic tests for heteroscedasticity, residual normality, and autocorrelation confirmed that the classical regression assumptions were met, validating the model for prediction. The study highlights the need for equitable agrarian reform, improved access to capital and technology, and strengthened farmer institutions as key to enhancing welfare. These findings provide crucial evidence for formulating inclusive and sustainable agrarian policies and agricultural development in Aceh.